Uji aktivitas antibakteri formulasi sediaan sabun padat transparan ekstrak daun belimbing wuluh (Averrhoa bilimbi L.) terhadap bakteri Cutibacterium acnes - Siti Aisyah Jamil; Minda Sari Lubis; Haris Munandar Nasution; Yayuk Putri Rahayu (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Acne is a skin disease that begins with an increase in sebum production which is exacerbated by an attack by the Cutibacterium acnes bacteria. Currently, there are many anti-acne preparations, one of which is in the form of soap, but only a few contain natural herbs. One plant that has an active substance or agent that has the potential to prevent and treat acne leaves belimbing wuluh (Averrhoa bililmbi L.) with its antibacterial properties. Besides having the potential to prevent and treat acne, this plant is also very easy to find in Indonesia. This research was conducted to see whether starfruit leaf extract could be formulated as soap preparation and whether it had antibacterial properties against Cutibacterium acnes. The research method for fresh starfruit leaves was made into Simplicia and extracted using 96% ethanol, phytochemical screening was carried out on fresh starfruit leaves and extracts. Transparent solid soap formulation with belimbing wuluh leaf extract with concentrations of 2.5%, 5%, and 7.5%. Evaluation preparations included physical quality tests, pH tests, foam height and stability tests, skin moisture tests, irritation tests, Panelist preference tests, and antibacterial activity against Cutibacterium acnes. The results and conclusions show that fresh starfruit leaves and extracts contain compounds belonging to class alkaloids, flavonoids, saponins, tannins, steroids/triterpenoids, and glycosides. Belimbing wuluh leaf extract can be formulated into transparent solid soap preparation, has a distinctive aroma extract, is homogeneous, pH 9-11, with spreadability 26-29mm. Antibacterial activity included the insensitive category at all concentrations. The panelist's preferred formula was preparation with a concentration of 2.5%